Critical Analysis of Living Law Formulation in Law No. 1 of 2023 Concerning the Criminal Code: Towards Law Reform to Realize Justice with the Spirit of Pancasila - Hardinanto, Aris; Arief, Barda Nawawi; Setiyono, Joko; Fernando, Zico Junius; Sabrina, Nahdiya (Universitas Negeri Semarang, 2024)
The government is trying to reform national law in the field of criminal law by drafting a Criminal Code Bill (RUU KUHP) to replace Wetboek van Strafrecht. The culmination of this preparation was the promulgation of the Criminal Code Bill on January 2, 2023, through Law No. 1 of 2023 concerning the Criminal Code (KUHP). However, there are not many articles that discuss the process and critical analysis of living law formulation as stated in the provisions of Article 2 of the Criminal Code and their explanations. The research method used was legal research with statute, historical, comparative legal, and conceptual approaches. The results of this research conclude that the living laws are formulated inconsistently in terms of scientific substance. In order to make this formulation can realize justice based on Pancasila, it can be achieved in several ways. First, there is a need to reinterpret living legal concepts by involving experts in customary law, legal anthropology, legal sociology, and interdisciplinary legal researchers. Second, redefining the meaning of law that lives within the body of the Criminal Code is not limited to customary law, especially the principle of legality, but also includes customary law and traditional laws in traditional societies. Third, formulating formal law/criminal procedural law as the enforcer of material criminal law/National Criminal Code by re-establishing and recognizing customary courts in the Indonesian criminal justice system whose application in society is to realize the fifth principle of social justice for all Indonesian people from Pancasila.